One-pot synthesis of mixed superphanes with CpCo-capped cyclobutadiene- and cyclopentadienone rings - Roers, Rolf; Rominger, Frank; Gleiter, Rolf (Tetrahedron letters, 1999)
A one-pot synthesis of mixed superphanes is reported in which CpCo-capped cyclobutadiene- and cyclopentadienone rings are connected by four pentamethylene and four heptamethylene chains, respectively.
Gesehen am 13.11.2020